Evaluation of Arabic Learning Outcomes Using Google Form During School Quarantine Due to Covid-19 Pandemic - Muhammad Thohir; Kiki Cahya Muslimah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Covid 19 is an extraordinary disease. The impact of this pandemic has paralyzed many sectors; one of them is education. Schools are closed and replaced with online learning. Facilities needed during the process of online are the availability of gadgets, internet quota, as well as online media that are compatible. One of these is Google Form. This study aims to know and explain the procedures on the use of learning outcome evaluation by the students of class X in SMA Muhammadiyah 4 Surabaya using google form during school quarantine due to covid 19 pandemic. This study uses descriptive qualitative method with data collection technique of questionnaires and interview. Study subjects were students of class X SMA Muhammadiyah 4 Surabaya.The results of this study showed that the requirements in using Google Form is only to have gadget, google account and internet quota. In the front menu of google form there are two parts namely Question and Responses. Switch from the Questions tab to the Responses tab in your form editor to see current responses to your form and link it to a spreadsheet. Then click on the three dots next to “+” then select download responses. From the spreadsheet, it can obtain complete information about timestamp, email address, name, class, score, and answers to questions by students orderly and automatically. Keywords: Google Form, Student Learning Outcome, Arabic.